KARAKTERISTIK SPRAY BAHAN BAKAR CAMPURAN MINYAK DIESEL DAN BIODIESEL CALLOPHYLLUM INOPHYLLUM - Muhammad Lutfi Azis; Lukman Hakim; Nasrul Ilminnafik (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2020)
The characteristic of spray largely determines of combustion quality. Before testing the fuel of diesel engine, characteristic of spray is needed to know. Biodiesel made from nyamplung seeds (callophyllum inophylum) mixed with diesel oil for spray characteristics test. The research was conducted at 1 atm ambient pressure, 15 MPa injection pressure. The fuel used Oil diesel added biodiesel variation B0, B20, B30, dan B100. The fuel mixture sprayed by nozzle tester and recorded using a 480 fps camera at 224x168 resolution to cognize spray tip penetration and spray angle. The result of research showing viscosity of fuel mixture has huge impact on spray characteristic. At high viscosity, longer spray tip penetration longer and smaller spray angle. Its affects the homogeneity of the mixture of fuel and the air. Keywords: spray characteristic, biodiesel, callophyllum inophylum